Characteristics of Nonunion Fractures in Patients with Antebrachial Fractures at dr. Mohamad Soewandhie General Hospital Surabaya 2021-2022: A Retrospective Study - Tasya Monica; Bimo Sasono; Cempaka Harsa Sekarputri (Journal Orthopaedi and Traumatology Surabaya)
Background: Nonunion, a complication of fracture healing, can lead to patient morbidity. Contributing factors include age, gender, fracture type, multiple fractures, infection, prolonged nonsteroidal anti-inflammatory drug (NSAID) use, smoking, nutritional status, and history of chronic disease. This study aims to determine the prevalence and characteristics of nonunion antebrachial fractures at dr. Mohamad Soewandhie General Hospital Surabaya.